Pengaruh Variasi Fraksi Massa Terhadap Kekuatan Bending Dan Morfologi Biokomposit Serat Bambu Tali Dengan Matriks Resin Epoxy - M. T.,, Joshua; Kencanawati, C I P Kusuma; Adnyana, I W Bandem (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract Bamboo is one of the alternative non-timber raw materials that are available in large quantities. Bamboo is a long fiber and has advantages in terms of harvesting, it only takes 3-4 years to be harvested compared to the fastest growing types of wood trees which takes 8-20 years. Composite is one way to take advantage of the function of bamboo. Bamboo is still very rarely used as the main material of composite. Composite is a new material from engineering which consists of two or more material where the characteristics of the material are different. Therefore, bamboo will be used as a reinforcing composite material which will be combined with epoxy resin as the matrix. This study aims to determine the physical and mechanical characteristics of bamboo fiber and epoxy resin composite with variations of bamboo fiber 10%, 15%, and 20%. where the tests carried out are bending tests and SEM tests. The results of the bending test showed that bamboo fiber with an epoxy resin matrix with a variation of 20% fiber had the highest bending strength value with the stress and strain values respectively 82,54 Mpa, 0.0153 mm/mm and also supported through SEM test which showed the bond between bamboo fiber and epoxy resin matrix is the one looks the most homogeneous compared to other fiber variations. Keywords: Composite, resin epoxy, bamboo fiber